2021
DOI: 10.7717/peerj.11852
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of crop tree management on undergrowth plant diversity and soil physicochemical properties in a Pinus massoniana plantation

Abstract: Background Soil and understory vegetation are vital components of forest ecosystems. Identifying the interaction of plantation management to vegetation and soil is crucial for developing sustainable plantation ecosystem management strategies. As one of the main measures of close-to-nature management of forest plantation, few studies have paid attention to the effect of crop tree management on the soil properties and understory vegetation. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Consequently, the understory vegetation receives abundant growth space, water, and heat, which is beneficial for nutrient and biomass accumulation by plants by making complete use of all kinds of resources (Márialigeti , 2016). The TN content is known to be the main limiting factor for plant growth and is closely related to the understory plant diversity (Lucasborja and Delgadobaquerizo, 2019;Lyu et al, 2021b), which was also observed in this study (Figure 1). We observed that the understory plant diversity was significantly affected by the available nutrients and TN content.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Consequently, the understory vegetation receives abundant growth space, water, and heat, which is beneficial for nutrient and biomass accumulation by plants by making complete use of all kinds of resources (Márialigeti , 2016). The TN content is known to be the main limiting factor for plant growth and is closely related to the understory plant diversity (Lucasborja and Delgadobaquerizo, 2019;Lyu et al, 2021b), which was also observed in this study (Figure 1). We observed that the understory plant diversity was significantly affected by the available nutrients and TN content.…”
supporting
confidence: 80%
“…A plausible reason could be that the soil environment of small gaps responds more quickly to interference in the forest than medium gaps, and small gaps are more conducive to the accumulation of soil phosphorus and increased plant diversity in the herb layer. As plants directly use inorganic phosphorus, phosphorus is a limiting factor for plant growth (Lyu et al, 2021b), which requires the hydrolysis of organophosphorus compounds by bacterial and fungal phosphatases prior to absorption by plants (George et al, 2002). Muscolo et al (2007) reported that phosphatase activity gradually decreases in plots with medium or large gaps, which is consistent with the reduction in the phosphorus content.…”
Section: E Ects Of Forest Gaps On Forest Managementmentioning
confidence: 83%
“…Previous studies have shown that, compared with poplar, reed has a higher underground biomass development, more prosperous root system, and is more difficult to decompose than poplar litter ( Monti and Zatta, 2009 ; Chimento and Amaducci, 2015 ), which makes more biological residues in the root system of reed and resulting in higher SOM. Moreover, understory plants were significantly correlated with the SOM ( Abebe et al, 2020 ), the lack of understory plants would lead to low carbon storage in plantations ( Lyu et al, 2021 ). The litter accumulated under the poplar plantation will cause direct physical obstacles to the germination of understory plants ( Ellsworth et al, 2004 ; Yu et al, 2021a ), and will also directly or indirectly affect the survival and renewal of understory plants by affecting the microenvironment such as light, temperature, and humidity, thereby reducing the SOM content ( Graae and Heskjær, 1997 ; Esteso-Martínez and Gil-Pelegrín, 2004 ; Bo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The P. massoniana plantation comprises a single tree layer; the shrub layer is primarily composed of Mallotus barbatus (Wall. ), Quercus serrata Thunb, and Cinnamomum camphora; and the herb layer is predominantly covered with ferns [7].…”
Section: Study Site and Sampling Designmentioning
confidence: 99%
“…Crop-tree thinning, a specialized method, achieves this by increasing the proportion of high-quality trees (crop trees) while removing similar-sized trees (e.g., low-forked and undesirable forms) that have limited economic value and lack a competitive position [5]. Although many studies have explored the impact of crop-tree thinning on stand growth structure [6] and plant diversity [7] in forest plantations, they often overlook the interaction of the aboveground vegetation community and the underground microbial community. Understanding this relationship is crucial in comprehending the transformation of inefficient plantations and the consequent effects on ecosystem restoration through crop-tree thinning.…”
Section: Introductionmentioning
confidence: 99%